2019
DOI: 10.4187/respcare.06419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Forced and Slow Vital Capacity Maneuvers in Defining Airway Obstruction

Abstract: BACKGROUND: Obstructive lung disease is diagnosed by a decreased ratio of FEV 1 to the vital capacity (VC). Although the most commonly used VC is FVC, American Thoracic Society guidelines suggest alternative VCs, for example, slow VC (SVC), may offer a more-accurate evaluation of breathing capacity. There is recent evidence that using only FEV 1 /FVC underrecognizes obstruction in subjects at high risk and who are symptomatic. Previous studies have indicated that healthy individuals show a minimum difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…28 Although SVC and FVC in theory should be the same in a healthy population with normal lungs, SVC usually is larger than FVC, especially in obese people or those with airways disease. 29,30 In individuals with no obstructive lung disease, the difference between SVC and FVC increases with increasing BMI and age. 29,30 Current lung function test interpretation guidelines acknowledge that inspiratory or expiratory SVC may be a better estimate of VC than FVC, but they do not provide specific recommendations regarding whether SVC should be used to calculate the FEV 1 to VC ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Although SVC and FVC in theory should be the same in a healthy population with normal lungs, SVC usually is larger than FVC, especially in obese people or those with airways disease. 29,30 In individuals with no obstructive lung disease, the difference between SVC and FVC increases with increasing BMI and age. 29,30 Current lung function test interpretation guidelines acknowledge that inspiratory or expiratory SVC may be a better estimate of VC than FVC, but they do not provide specific recommendations regarding whether SVC should be used to calculate the FEV 1 to VC ratio.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In individuals with no obstructive lung disease, the difference between SVC and FVC increases with increasing BMI and age. 29,30 Current lung function test interpretation guidelines acknowledge that inspiratory or expiratory SVC may be a better estimate of VC than FVC, but they do not provide specific recommendations regarding whether SVC should be used to calculate the FEV 1 to VC ratio. 6 Nevertheless, professional organizations have proposed the FEV 1 to VC ratio instead of the FEV 1 to FVC ratio as a diagnostic criterion for COPD at certain times.…”
Section: Discussionmentioning
confidence: 99%
“…Using the FEV1/SVC criteria, the prevalence of obstruction increased from 26.1 to 45% and 566 additional cases of obstruction were diagnosed who otherwise had a preserved FEV1/FVC showing that SVC-based diagnostic criteria can lead to earlier detection of disease with improved clinical outcomes. 16 Saint-Pierre et al studied the PFTs of 13,893 adult patients with a FEV1/FVC and TLC at or above the lower limit of normal. It showed that performing the slow maneuver of SVC was able to uncover the airflow limitation which was missed by FEV1/FVC.…”
Section: Huprikar Et Al Performed a Retrospective Analysis Of 2710mentioning
confidence: 99%
“…1 The differences between FVC and SVC are affected by variables like body mass index (BMI), age and gender. 16 Fortis et al studied the effect of BMI on the difference between FVC and SVC by retrospectively reviewing the PFTs of 1805 subjects. The results showed that in the patients with a normal BMI (BMI<25 kg/m 2) with no obstruction, FVC was larger than SVC whereas in overweight and obese patients, the SVC was significantly larger than FVC and the SVC-FVC difference positively correlated with the BMI.…”
Section: Introductionmentioning
confidence: 99%
“…7 Also, obese subjects or those with obstructive disease with a greater degree of emphysema yield SVC larger than FVC. 8 Vital capacity measurements have a flow-dependence more pronounced in subjects with COPD, which results in a truncation of expiratory volume in forced maneuvers. Emphysema may result in expiratory airway collapse, which implies increase in SVC-FVC difference; a larger volume of air can be mobilized by the measurement of vital capacity through an unforced maneuver, because it produces lower intrathoracic pressure.…”
mentioning
confidence: 99%